2023
DOI: 10.3390/technologies11010010
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Hybrid CNN Classification Model for Tomato Crop Disease

Abstract: Tomato plants are vulnerable to a broad number of diseases, each of which has the potential to cause significant damage. Diseases that affect crops substantially negatively impact the quantity and quality of agricultural products. Regarding quality crop maintenance, the importance of a timely and accurate diagnosis cannot be overstated. Deep learning (DL) strategies are now a critical research field for crop disease diagnoses. One independent system that can diagnose plant illnesses based on their outward mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The major objective of FGVC in the agriculture sector is to accurately identify informative regions in the picture. This has been a problem in previous computational work [12,13], for example where it was found that the model had trouble zeroing in on informative regions, leading to poor classification accuracy. When it comes to agriculture's sustainability, plant diseases have historically been one of the biggest obstacles.…”
Section: Figure 1 Tomato Leaf Samples With Various Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…The major objective of FGVC in the agriculture sector is to accurately identify informative regions in the picture. This has been a problem in previous computational work [12,13], for example where it was found that the model had trouble zeroing in on informative regions, leading to poor classification accuracy. When it comes to agriculture's sustainability, plant diseases have historically been one of the biggest obstacles.…”
Section: Figure 1 Tomato Leaf Samples With Various Diseasementioning
confidence: 98%
“…However, farmers and gardeners aren't always successful in achieving optimal plant development [12]. Sometimes the tomatoes will not mature at all, and other times they will ripen but have unsightly black patches on the bottom that look sick.…”
Section: Introductionmentioning
confidence: 99%
“…The validation set is utilised to estimate the network's effectiveness on unknown data during training to enhance the network's performance. The test set provides a final, objective assessment of the network's performance after training on unseen data [31].…”
Section: Split Collectionmentioning
confidence: 99%
“…Plant diseases present a crucial obstacle to the growth of agriculture in every country, resulting in significant yearly financial losses ( Mitra, 2021 ). Plant disease detection has developed into a substantial area of study in pattern recognition and contemporary agricultural development due to developments in machine learning technology ( Roy and Bhaduri, 2021 ; Albattah et al., 2022 ; Sanida et al., 2023 ). Early plant disease identification approaches used a support vector machine (SVM) ( Rahman et al., 2023 ; Thangavel et al., 2023 ), artificial neural network (ANN) ( Attallah, 2023 ), and SVM method for disease diagnosis under segmented plant disease spots.…”
Section: Introductionmentioning
confidence: 99%